Rule of the Aurora King - Tuli, Nisha J. (2023)
""I am not his conquest. I am not his to claim. I am my own castle." Freed from the golden clutches of the Sun King, Lor now finds herself in the hands of Nadir, the Aurora Prince. Convinced she's hiding something, he's willing to do whatever it takes to make her talk. But Lor knows the value of secrets -- she's been keeping them her entire life -- and she's not letting hers go without a fight. When Lor and Nadir team up to search for a lost item that holds the key to her past and her future, she isn't sure if she can trust him. All she knows is she won't fall for his promises and make the same mistakes again. Lor also hasn't forgotten her vow to destroy the Aurora King. As Atlas hunts her across Ouranos, Lor plots to bring down the Imperial Fae who took everything. But she soon realizes that the future of the continent is about so much more than just her shattered legacy. Rule of the Aurora King is the second book in the Artefacts of Ouranos series and combines romance, intrigue, action, and adventure. If you love enemies to lovers, fated mates, and fake dating, don't miss this exciting next installment!" --
Keywords: Queens -- Fiction; Princes -- Fiction; Secrecy -- Fiction; Kings and rulers -- Fiction; Revenge -- Fiction; Man-woman relationships -- Fiction; Reines -- Romans, nouvelles, etc; Princes -- Romans, nouvelles, etc; Secret -- Romans, nouvelles, etc; Rois et souverains -- Romans, nouvelles, etc; Vengeance -- Romans, nouvelles, etc; Relations entre hommes et femmes -- Romans, nouvelles, etc; Kings and rulers; Man-woman relationships; Princes; Queens; Revenge; Secrecy